Problem-based and related learning approaches in family medicine residency: A scoping review of four countries - Clemens, Megan; Boparai, Josheil Kaur; Dawe, Russell; Avery, Susan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Background: Postgraduate medical education (PGME) bridges the transition from medical school to independent practice. Problem-based learning (PBL), widely used in undergraduate medical education, has emerged as a promising alternative to traditional lectures in PGME. However, its impact on family medicine training remains unclear.Objective: In this scoping review, we describe the use of PBL in family medicine PGME programs and examine its educational and healthcare-related outcomes.Methods: Using Arksey and O'Malley's methodological framework, we conducted a scoping review of PubMed, Embase, PsycINFO, ERIC, Web of Science, and ProQuest in January 2025. Two reviewers independently screened articles, extracting and synthesizing data according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR).Results: Twelve studies met inclusion criteria, illustrating diverse PBL delivery methods in family medicine PGME. Programs integrated PBL as standalone sessions, an adjunct, or blended with traditional methods. Learning groups often included mixed specialties (e.g., family medicine and internal medicine) and varied learner levels (e.g., residents and attending physicians). Most studies reported high learner satisfaction and improved perceptions of topics; however, objective assessments of knowledge, pre- and post-PBL, showed no significant improvement. Limited data on behavior and patient outcomes suggested potential benefits.Conclusion: PBL in family medicine PGME appears to enhance engagement and satisfaction but shows mixed educational outcomes. Further research is needed to determine its optimal role in training.